Can Hemoglobin-Hematocrit Relationship Be Used to Assess Hydration Status? - Hosti Hayuanta, Hubertus (PT. Kalbe Farma Tbk., 2016)
There is an opinion that if the hematocrit is lower than multiplied hemoglobin (Hct< 3 x Hb), the patient is overhydrated, and if it is higher (Hct> 3 x Hb), the patient is dehydrated. This practice is flawed. Hemoglobin-hematocrit relationship is not affected by a patient’s hydration status, and thus its alteration cannot be used to assess it. The relationship can only be altered if the red blood cells (RBCs) are abnormal, or look altered because of technical factors.Instead of multiplying hemoglobin value and comparing it to the hematocrit, a quicker way to assess is to evaluate the mean corpuscular hemoglobin concentration (MCHC). Clinicians can still predict hydration status by comparing the hematocrit to its baseline value or the laboratory’s reference range, by physical examination, or use other laboratory tests such as urine specifi c gravity and osmolality.